Hubungan nilai kerja dengan jantina, umur dan pengalaman mengajar guru pelatih - Kasa, Zakaria; Md. Aroff, Abdul Rahman (Universiti Putra Malaysia Press, 1997)
In order to be successful in his work, a person should have not only knowledge and skills, but also good work values. The study explored twelve work values of trainee teachers of Universiti Pertanian Malaysia (UPM) and their relationships with gender, age and teaching experience. In general, trainee teachers of UPM had good work values. They considered self-development, economic reward and job security as very important values, whereas creativity, working conditions, life style and autonomy were considered moderately important. Values like variety, authority, social relationship, risk, and prestige were not very important to them. In addition, significantly low relationships exist between work values and age and teaching experience. Young trainee teachers without teaching experience were found to have better work values than experienced trainee teachers. Male trainee teachers were found to value creativity and authority more than female trainee teachers. Trainee teachers without teaching experience were also found to value variety, risk and prestige more than experienced trainee teachers. Age was found to have negative and low but significant relationships with life style, authority, risk and prestige. This relationship showed that as trainee teachers grew older, these values became less important to them. Based on the findings of the study, it is suggested that rewards should be given to teacher's in order to attract more of the younger generation to become teachers, teachers should be given more autonomy, teachers should be motivated to use their own creativity, and younger teachers should be given challenging tasks.